Exploring the Architecture of the Amir Timur Museum as Inspiration for Avant-Garde Fashion Design Using Quilting Manipulation - Amelia Marsya Akilaray; Indarti Indarti (Journal of Creative Industries and Vocational Innovation, 2026)
This article discusses the design process of avant-garde fashion inspired by the architecture of the Amir Timur Museum and analyzes the final garment produced using quilting techniques. The visual inspiration was derived from the museum's monumental architectural characteristics, geometric ornaments, dome structure, and symbolic values of glory, strength, and historical identity. These visual and symbolic values were translated into fashion through the exploration of silhouette, structure, color, material, and quilting manipulation as the main surface and structural technique. This study used the Double Diamond method, consisting of four stages: Discover, which involved identifying sources of ideas through literature study and visual observation; Define, which formulated the design concept through a moodboard; Develop, which focused on illustration and design development; and Deliver, which realized and evaluated the final product. The study was conducted in the Fashion Laboratory, Faculty of Vocational Studies, Universitas Negeri Surabaya. Data were collected using observation sheets involving three Fashion Design experts and were analyzed using mean scores. The final product showed that architectural elements of the Amir Timur Museum could be transformed into a structured avant-garde garment through quilting, pattern construction, material selection, and decorative detailing. Expert validation produced mean scores ranging from 4.33 to 5.00, indicating that the design quality was in the very good category.